Representation of God in A.A. Navis's Short Stories: A Hermeneutics Review - Muzaki, Ahmad; Rahman, Gohar (Lingua : Journal of Linguistics and Language, 2024)
A.A Navis is an Indonesian writer who is famous for his works with transcendental god elements. The unique way of conveying messages in his short stories often makes readers stutter in grasping the true meaning. This research examines A.A Navis' short stories which have a divine theme and contain prophetic elements. Some of the short stories are Robohnya Surau Kami (The Collapse of Our Surau), Man Rabbuka, Datang dan Perginya (Coming and Going), Dokter dan Maut (Doctor and Death, and Yang Datang di Hari Lebaran (Who Came on Eid Day). This research aims to describe the representation of God in A.A Navis' short stories through a hermeneutical review. The research method used in this research is descriptive qualitative. The results of this research depict that A.A Navis' short stories represent God as; (1) the best judge, (2) not thirsty for praise, (3) not wanting to cause trouble to his servant, (4) the owner of the highest power, (5) the giver of rewards, (6) the forgiver, (7) the owner of death, and (8) ) answerer of prayers. Apart from that, there are also divine values ​​and other messages conveyed in the short stories he wrote.